Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How do you taylor expand the function $F(x)={x\over \ln(x+1)}$ using standard results? (I know that WA offers the answer, but I want to know how to get it myself.) I know that $\ln(x+1)=x-{x^2\over 2}+{x^3\over 3}+…$ But I don't know how to take the reciprocal. In general, given a function $g(x)$ with a known Taylor series, how might I find $(g(x))^n$, for some $n\in \mathbb Q$?

Also, how might I evaluate expressions like $\ln(1+g(x))$ where I know the Taylor expansion of $g(x)$ (and $\ln x$). How do I combine them?

Thank you.

share|improve this question
    
I'm not sure there's a way to do it without re-calculating the coefficients. –  Alex Becker Feb 19 '12 at 9:36
    
I have figured this out. Thanks anyways. –  tycho Feb 19 '12 at 10:37

3 Answers 3

You can do this by long division:

$\dfrac{x}{x-{x^2\over 2}+{x^3\over 3}-\cdots} = 1 + \dfrac{{x^2\over 2}-{x^3\over 3}+\cdots}{x-{x^2\over 2}+{x^3\over 3}\cdots} = 1 + \frac{x}{2} + \dfrac{-{x^3\over 12}+\cdots}{x-{x^2\over 2}+\cdots} = 1 + \frac{x}{2} - \frac{x^2}{12} + \cdots $

share|improve this answer
    
Thank you, Henry. –  tycho Feb 19 '12 at 12:00

You have

$$F(x)=\frac{x}{\sum_{n\ge 1}\frac{(-1)^{n+1}}nx^n}=\frac1{\sum_{n\ge 0}{\frac{(-1)^n}{n+1}}x^n}=\frac1{1-\frac{x}2+\frac{x^2}3-+\dots}\;.$$

Suppose that $F(x)=\sum\limits_{n\ge 0}a_nx^n$; then you want

$$1=\left(1-\frac{x}2+\frac{x^2}3-+\dots\right)\left(a_0+a_1x+a_2x^2+\dots\right)\;.$$

Multiply out and equate coefficients:

$$\begin{align*} 1&=a_0\,;\\ 0&=a_1-\frac{a_0}2=a_1-\frac12,\text{ so }a_1=\frac12\,;\\ 0&=a_2-\frac{a_1}2+\frac{a_0}3=a_2-\frac14+\frac13=a_2+\frac1{12},\text{ so }a_2=-\frac1{12}\,; \end{align*}$$

and so on. In general $$a_n=\frac{a_{n-1}}2-\frac{a_{n-2}}3+\dots+(-1)^{n+1}\frac{a_0}{n+1}$$ for $n>0$, so

$$\begin{align*}&a_3=-\frac1{24}-\frac16+\frac14=\frac1{24}\;,\\ &a_4=\frac1{48}+\frac1{36}+\frac18-\frac15=-\frac{19}{720}\;,\\ &a_5=-\frac{19}{1440}-\frac1{72}+\frac1{48}-\frac1{10}+\frac16=\frac{29}{480}\;, \end{align*}$$

and if there’s a pattern, it isn’t an obvious one, but you can get as good an approximation as you want in relatively straightforward fashion;

$$F(x)=1+\frac{x}2-\frac{x^2}{12}+\frac{x^3}{24}-\frac{17x^4}{720}+\frac{29x^5}{480}+\dots$$

already gives two or three decimal places over much of the interval of convergence.

share|improve this answer
    
Thank you, Brian. –  tycho Feb 19 '12 at 11:59

Concerning the multiplicative inverse of $\ln(1+x)$ you may use the classical division (here $x$ is divided by $\ln(1+x)$ ) :

$\begin{array} {r|l} x +0 x^2+0 x^3 & x-\frac{x^2}2+\frac{x^3}3+\cdots \\ -x+\frac{x^2}2-\frac{x^3}3 & 1+\frac x2-\frac {x^2}{12}\\ \frac{x^2}2-\frac{x^3}3 & \\ -\frac{x^2}2+\frac{x^3}4 & \\ -\frac{x^3}{12} & \\ \end{array} $

So that $\displaystyle \frac x{\ln(1+x)}=1+\frac x2-\frac {x^2}{12}$


Concerning integer powers ($f(x)^n$ with $n\in \mathbb{N}$) just apply distributivity of multiplication $n-1$ times ($f(x)=\ln(1+x)$ here) :

$\ln(1+x)^2= \left(x-\frac{x^2}2+\frac{x^3}3+\cdots\right)\cdot\left(x-\frac{x^2}2+\frac{x^3}3+\cdots\right)$

$=x\cdot\left(x-\frac{x^2}2+\frac{x^3}3+\cdots\right)-\frac{x^2}2\cdot\left(x-\frac{x^2}2+\frac{x^3}3+\cdots\right)+\frac{x^3}3\cdots$

For higher powers use : $\ln(1+x)^3=\ln(1+x)^2\cdot \ln(1+x)$ and so on...

Sometimes it will be more convenient to rewrite the exponent in powers of $2$.
For example $\displaystyle f^9= f^{1+2^3}=f\cdot(((f^2)^2)^2$.


To compute $(1+f(x))^p$ you may use following expansion :
$(1+f(x))^p= 1+ p f(x)+ \frac{p(p-1)}{2!} f(x)^2 + \frac{p(p-1)(p-2)}{3!} f(x)^3+\cdots \binom{p}{k} f(x)^k+\cdots$

Note that you'll sometimes have to divide or multiply by a power of $x$ to apply these methods (in the division we replaced $\frac1{\ln(1+x)}$ by $\frac x{\ln(1+x)}$, here we have $1+f(x)$ so that when computing for example $(x+f(x))^p$ we may rewrite this as $x^p\cdot(1+\frac{f(x)}x)^p$).

For any power $p$ (or when $\ln(1+f(x))$ is simple) you may use :

$\displaystyle (1+f(x))^p=e^{p\cdot \ln(1+f(x))}=e^{p\cdot \left(f(x)-\frac{f(x)^2}2+\cdots\right)}$

share|improve this answer
    
Thank you, Raymond. –  tycho Feb 19 '12 at 12:00

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.